A Global Stocktake on Electricity Access and Gaps From NASA Black Marble Nighttime Lights - Srija Chakraborty; Olivia Alexander; Noah Kittner; Zhuosen Wang (Earth's Future, 2025)
Abstract Electricity is a basic human necessity. We are highly reliant on continuous access to electricity for our health, well‐being, and it remains essential for critical infrastructure, industries, and human development. Yet, there remains a gap in populations with access to electricity across the globe. Mapping where gaps in electrification are currently is vital to estimate the unmet energy demand to ensure universal access to electricity and modern fuels. To be informative, mapping of electricity access gaps is needed on a global scale but with spatially‐disaggregated granularity and it is non‐trivial to derive this spatially‐explicit data globally. Satellite observations have the unique vantage point of acquiring global observations with frequent updates and are collected in a standardized manner. Specifically, NASA Black Marble is the only openly available data set that derives corrected, global, daily nighttime lights (NTL) that are ideal for analyzing settlement pixels and electrification with its decade‐long records. We derive global maps of electrification at 1 km resolution using NTL time‐series from 2012 to 2022 and fill in the existing global knowledge gap using improved NTL retrievals from this corrected data set. We evaluate our analyses with global surveys at the national scale and observe high agreement, derive quality flags, and share the results as an open‐access data set. We analyze our data set to examine the areas with highest access gaps and discuss the potential of the data set to inform energy transition plans and electricity demand estimations for integrated assessment models that jointly evaluate the effects of climate change and energy transitions.